2017
DOI: 10.1186/s40104-017-0162-8
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses induced by lipopolysaccharide and lipoteichoic acid in primary goat mammary epithelial cells

Abstract: BackgroundInnate immune responses induced by in vitro stimulation of primary mammary epithelial cells (MEC) using Gram-negative lipopolysaccharide (LPS) and Gram-positive lipoteichoic acid (LTA) bacterial cell wall components are well- characterized in bovine species. The objective of the current study was to characterize the downstream regulation of the inflammatory response induced by Toll-like receptors in primary goat MEC (pgMEC). We performed quantitative real-time RT-PCR (qPCR) to measure mRNA levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 56 publications
7
45
1
Order By: Relevance
“…LPS could result in the activation of NF-jB, regulating the expression of inflammatory cytokines in mice embryonic fibroblast (Yamamoto et al 2003). LPS is one of the main stress sources used in the study of oxidative damage in BMECs and goat mammary epithelial cells to induce IL-1 production (Bulgari et al 2017;Wang et al 2017). Our previous research has established LPS-induced oxidative stress model of BMECs .…”
Section: Discussionmentioning
confidence: 99%
“…LPS could result in the activation of NF-jB, regulating the expression of inflammatory cytokines in mice embryonic fibroblast (Yamamoto et al 2003). LPS is one of the main stress sources used in the study of oxidative damage in BMECs and goat mammary epithelial cells to induce IL-1 production (Bulgari et al 2017;Wang et al 2017). Our previous research has established LPS-induced oxidative stress model of BMECs .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that, during murine post-lactational regression, mammary epithelial cells exhibit dramatic, Stat3-dependent, up-regulation of CD14, an innate immune component [ 52 , 53 ]. In addition, cultured bovine and caprine mammary epithelial cells have been shown to express TLR2 and TLR4 mRNA, and responses of mammary epithelial cells to stimulation with bacterial cell wall components, or other agents with the potential to cause mastitis, such as Prototheca spp., result in elaboration of a plethora of cytokines and other inflammatory mediators [ 54 , 55 ]. These findings suggest that mammary epithelial cells, across species, have a critical role to play in the mammary immune microenvironment although clearly much of the current evidence for this assertion is derived from studies using rodent mammary epithelial cells in vitro, and from in vivo studies of rodent models.…”
Section: Comparative Mammary Gland Immunologymentioning
confidence: 99%
“…The CCL2 generally induces inflammatory responses through monocyte infiltration, but it also acts as an anti-inflammatory agent at low concentrations (Flaishon et al, 2008). The expression of CCL2 in mammary epithelial cells of goats increases in response to LPS, but it is unknown whether CCL2 can control mastitis in cows (Bulgari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%